Acute and 28-day sub-acute intravenous toxicity studies of 1’-S-1′-acetoxychavicol acetate in rats - Abdalla, Yasir Osman Ali; Nyamathulla, Shaik; Shamsuddin, Noorasyikin; Arshad, Norhafiza Mohd; Mun, Kein Seong; Awang, Khalijah; Nagoor, Noor Hasima (Elsevier, 2018)
1′-S-1′-acetoxychavicol acetate (ACA) has been previously reported to reduce tumor volume in nude mice, at an effective dose of 1.56 mg/kg body weight. However, the detailed toxicological profile for ACA has not yet been performed. Herein, we investigated the toxicity of intravenous administration of ACA in male and female Sprague-Dawley rats, both acutely (with single doses of 2.00, 4.00 and 6.66 mg/kg body weight, for 14 days), and sub-acutely (with weekly injections of 0.66, 1.33, and 2.22 mg/kg, for 28 days). In both toxicity studies, treatment with ACA did not affect behavior, food/water intake or body weight, nor did it induce any changes in clinically relevant hematological and biochemical parameters or mortality, suggesting that the LD 50 of ACA was higher than 6.66 mg/kg body weight, regardless of sex. Sub-acutely, there was however, mild focal inflammation of kidneys and lobular hepatitis, but these were not associated with significant functional adverse effects. Therefore, the no-observed-adverse-effect level (NOAEL) for intravenous administration of ACA in the present 28-day sub-acute study was 2.22 mg/kg body weight, in both male and female rats. These findings provide useful information regarding the safety of ACA use in a healthy, non-tumor-bearing rat model.